A new blowup criterion for strong solutions of the three-dimensional isentropic compressible micropolar fluid. (May 2023) - Hong, Ping; Hou, Xiaofeng
Abstract: In this paper, we establish a new blowup criterion for the strong solution to the three-dimensional micropolar fluid equations with vacuum in a bounded domain Ω ⊂ R 3 . Specifically, we obtain the blowup criterion in terms of ‖ P ‖ L t ∞ B M O x, and it is independent on the velocity of rotation of the microscopic particles. Moreover, the appearance of vacuum could be allowed.